Challenges and achievements in historical re-creations: El equilibrio entre autenticidad y los valores actuales: el caso del 550 aniversario de Isabel I de Castilla en Segovia - Muñoz Sastre, Daniel; Rodrigo-Martín, Isabel (Street Art & Urban Creativity, 2025)
Historical re-creations have become elements that stimulate cultural activity in the places where they take place. The commemoration in Segovia (Spain) of the 550th anniversary of the proclamation of Isabella I as Queen of Castile is an example of this type of event. To commemorate this event, the city council of the city in which the event was held organised a programme of activities. This paper presents a qualitative study of this commemoration through a review of documents, and participatory observations of the organisation of these events. This research demonstrates the characteristics of this type of event and the challenge of those who organise it. The challenge is none other than to find harmony between historical authenticity and adaptation to current values, ensuring that the celebrations continue to be meaningful for future generations.